2018
DOI: 10.1177/0020731418770956
|View full text |Cite
|
Sign up to set email alerts
|

Needs in Service Provision for Oral Health Care in Older People: A Comparison Between Greater Manchester (United Kingdom) and Utrecht (the Netherlands)

Abstract: Retaining natural teeth for longer, together with increasing care dependency in the elderly, has the potential to hamper adequate oral self-care and service provision. The aim of this qualitative study was to compare and contrast views from a multi-stakeholder perspective on the future priorities for oral health care services of older people in the United Kingdom and the Netherlands. A participatory setting partnership was undertaken with 4 key stakeholder groups in the United Kingdom and the Netherlands. A fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The participants presented various medical conditions and disabilities. Ten qualitative studies were found for individuals with cognitive or physical impairment, [34][35][36][37][38][39][40][41][42][43] six for people with mental illness, [46][47][48][49][50][51] five for elderly persons with comorbidities, [24][25][26][27][28] three for adults with dementia, [31][32][33] two for persons who had received head and neck cancer treatment, 44,45 two for individuals in palliative care, 52,53 one for adults with cardiovascular disease, 30 , one for stroke survivors. 29 The data extracted did not bring to light similarities or differences between the population subgroups.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The participants presented various medical conditions and disabilities. Ten qualitative studies were found for individuals with cognitive or physical impairment, [34][35][36][37][38][39][40][41][42][43] six for people with mental illness, [46][47][48][49][50][51] five for elderly persons with comorbidities, [24][25][26][27][28] three for adults with dementia, [31][32][33] two for persons who had received head and neck cancer treatment, 44,45 two for individuals in palliative care, 52,53 one for adults with cardiovascular disease, 30 , one for stroke survivors. 29 The data extracted did not bring to light similarities or differences between the population subgroups.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Oral health of older adult CRs is an important objective stressor for family caregivers, which need to be aware of and pay specific attention to in practice. Fortunately, some older adults themselves recognised the importance of daily oral healthcare and asked help from caregivers when they were not able to do it themselves (Everaars et al, 2015). Actions and resources to improve the oral health of older adults also need to be in place because of its potential in lowering caregiving stress and leading to an improved quality of life and quality of the care provided by family caregivers.…”
Section: Programs and Policy Implicationsmentioning
confidence: 99%
“…4,5 Consequently, oral healthcare remains a neglected part of nursing care in nursing homes, hospitals, and community care. [6][7][8][9] Oral health care is important to prevent the development of complex oral diseases and dental problems. 10 Worldwide, 56%-85% of older people suffer from inflammations of the gums and surrounded tissues (periodontal diseases).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the availability of assessment tools, intervention sets, and routes to refer to experts are not implemented in daily nursing practices 4,5 . Consequently, oral healthcare remains a neglected part of nursing care in nursing homes, hospitals, and community care 6–9 …”
Section: Introductionmentioning
confidence: 99%